A propos de l'espèce Phumosia vittata (Curran, 1927) de la faune de Nigeria (Diptera, Calliphoridae) - Lehrer, A.Z.; Goergen, Georg E. (2006)
On the species Phumosia vittata (Curran, 1927) of the fauna of Nigeria (Diptera, Calliphoridae). One gives the general description of the species Phumosia vittata (Curran) and one presents, for the first time, the details of its male genitalia.